Development and evaluation of bamboo nanocellulose PVDF mixed matrix membrane for water purification - Kuok King, Kuok; Mohd. Elfy, Mersal; Rezaur, Rahman; Khairul Anwar, Mohamad Said; Chiu, Po Chan; Anthonette, James (Elsevier B.V., 2025)
This paper focuses on developing and evaluating bamboo nanocellulose-incorporated PVDF mixed matrix membranes for water purification. We highlight the potential of using bamboo, a renewable and biodegradable resource, to create advanced nanofiltration membranes. These membranes were tested for their effectiveness in removing contaminants such as heavy metals, organic compounds and dyes from water. Five types of membranes were developed, namely a pristine membrane (PVDF), PVDF-1 % nanocellulose membrane (NCM), PVDF-2 %NCM, PVDF-3 %NCM, PVDF-4 %NCM, and PVDF-5 %NCM. These had 1 %, 2 %, 3 %, 4 %, and 5 % nanocellulose-incorporated nanocomposite membrane, respectively. Water permeability and dye rejection performance increased with increasing nanocellulose content from 1 % to 4 %. PVDF-4 %NCM demonstrated the best balance of water